Evaluating an Instrument to Quantify Attitude to the Subject of Physiology in Undergraduate Health Science Students - Brown, Stephen; White, Sue; Bowmar, Alex; Power, Nicola (Journal of University Teaching and Learning Practice, 2017)
The attitude toward a subject contributes to both academic engagement and success at university, yet it is not routinely measured in undergraduate students. Therefore, in two consecutive introductory courses in Human anatomy and physiology (HAP 1, n= 239, and HAP 2, n=329), an instrument to quantify undergraduate students’ attitude to the subject of physiology (ASPI) was evaluated using exploratory factor analysis (EFA). In both HAP 1 and HAP 2, EFA indicated two latent components – affective (component 1) and cognitive (component 2). Items comprising each component were consistent for both courses, and alpha coefficients >0.7 indicated good internal consistency. Differences in affective attitude and cognitive attitude between HAP 1 and HAP 2 indicated that students had a more negative attitude to physiology in HAP 2. The ASPI may be a useful instrument to quantify affective and cognitive attitude in undergraduates studying physiology, thus complementing routine assessment of academic performance.